2010
DOI: 10.1177/1933719110376979
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk Factors Associated With Subtypes of Uterine Leiomyomata

Abstract: Although the 2 focal UL subtypes had similar risk factor profiles, the diffuse UL subtype appeared to have a distinctive risk profile with regard to current smoking. Further study of the diffuse heterogeneity seen with uterine ultrasound is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
1
21
2
Order By: Relevance
“…31,32 The Uterine Fibroid Study evaluated risk factors with different sub-types of uterine leiomyomata categorized by tumor location (submucosal, intramural, subserosal, and diffuse disease); this study demonstrated increased risk of diffuse uterine leiomyomatosis in tobacco smokers. 33 However comparisons between air pollution exposures and tobacco exposures must be undertaken cautiously as studies have suggested that tobacco smoke has an anti-estrogenic effect, 34,35 where limited in vitro studies have suggest estrogenic effects of air pollution. 16 …”
Section: Discussionmentioning
confidence: 99%
“…31,32 The Uterine Fibroid Study evaluated risk factors with different sub-types of uterine leiomyomata categorized by tumor location (submucosal, intramural, subserosal, and diffuse disease); this study demonstrated increased risk of diffuse uterine leiomyomatosis in tobacco smokers. 33 However comparisons between air pollution exposures and tobacco exposures must be undertaken cautiously as studies have suggested that tobacco smoke has an anti-estrogenic effect, 34,35 where limited in vitro studies have suggest estrogenic effects of air pollution. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Because mitotic activity in the myometrium is greatest during the luteal phase of the menstrual cycle [74], a longer history of cycling would be expected to increase UL risk. In support of this, most studies have shown that UL risk increases with earlier age at menarche [22, 29, 7581]. No studies have investigated the relation between late age at menopause and risk for UL.…”
Section: Etiologic Hypotheses and Risk Factorsmentioning
confidence: 99%
“…However, more recent case-control [79, 88] and prospective cohort studies [23, 97] find no such association. In the UFS, there was a positive relation of smoking with diffuse UL but not with submucosal or intramural/subserosal UL [81]. Tobacco components may inhibit aromatase [106] and shift estradiol metabolism toward less potent forms of estrogen [107, 108].…”
Section: Etiologic Hypotheses and Risk Factorsmentioning
confidence: 99%
“…1 Although benign, they can be a chronic condition for many women, as clinical symptoms may be present in up to 50% of those affected. 2,3 These symptoms can include heavy menstrual bleeding, prolonged periods, pelvic pressure symptoms, and reproductive dysfunction. 4 This significant morbidity during a woman's reproductive years has made fibroids the leading cause of hysterectomy in the United States.…”
mentioning
confidence: 99%